Review on Extraction of Medicinal Plants Constituents by Superheated Water - F Golmohamad; MH Eikani; S Shokrollahzadeh (Institue of Medicinal Plants, ACECR, 2008)
In this paper, we reviewed properties of superheated water, the basic principles of superheated water extraction (SWE) and its applications. Also, the required equipments, advantages and disadvantages of this method in relation to the conventional extraction processes e.g. steam distillation and Soxhlet, were explained. One of the novel applications of SWE is extraction of essential oils from medicinal plants. SWE is an environmental friendly, more efficient method and can be considered as a green chemical technology. In this regard, a laboratory extraction unit of SWE was designed fabricated and essential oils of some plants such as coriander, cumin and lavender were extracted.